Perlindungan Hukum Terhadap Merek Kerajinan Kulit Di Magetan - Murdianti, Dewi, Inayah.S.H., M.H (2017)
This study aims to determine how the implementation of the legal protection of leather goods brand in Magetan, barriers and how to overcome it. The research method using descriptive empirical jurisdiction. The data source consists of the primary data and secondary data, interview the legal data of primary, secondary and tertiary. Data were collected through the study of literature and field research (interviews), then the data is analyzed qualitatively. The brand is a sign that distinguishes the goods and / or services produced or provided by a person or legal entity in the trading of goods and / or services. Act No. 20 of 2016 on Marks also regulates the legal protection of brand, with the absence of legal protection brand, it can minimize the occurrence of violations of the same brand from others. Trademark registration must meet the requirements set by the legislation in force.